Towards a fairer platform economy: introducing the Fairwork Foundation - Graham, M; Woodcock, J (AU Press, 2018)
Increasingly greater numbers of people are now using apps, platforms, and websites to find and perform jobs. There are at least seven million platform workers that live all over the world, doing work valued at US$5 billion per year outsourced via platforms or apps (Kuek et al. 2015; Heeks 2017). Eleven percent of the labour force in the United Kingdom have already earned income from digital labour platforms (Huws and Joyce 2016), and it is predicted that by 2025, one third of all labour transactions will be mediated by digital platforms (Standing 2016).